Mean Reversion and Consumption Smoothing - Black, Fischer (Review of Financial Studies, 1990)
Stambaugh, and especially to Robert Merton for comments on a previous draft. This paper is part of NBER's research program in Financial Markets and Monetary Economics. Any opinions expressed are those of the author not those